Treatment responsiveness in KCNT1-related epilepsy - Fitzgerald, Mark P.; Fiannacca, Martina; Smith, Douglas M.; Gertler, Tracy S.; Gunning, Boudewijn; Syrbe, Steffen; Verbeek, Nienke; Stamberger, Hannah; Weckhuysen, Sarah; Ceulemans, Berten; Schoonjans, An-Sofie; Rossi, Massimiliano; et al. (Neurotherapeutics, 2019)
Pathogenic variants in KCNT1 represent an important cause of treatment-resistant epilepsy, for which an effective therapy has been elusive. Reports about the effectiveness of quinidine, a candidate precision therapy, have been mixed. We sought to evaluate the treatment responsiveness of patients with KCNT1-related epilepsy. We performed an observational study of 43 patients using a collaborative KCNT1 patient registry. We assessed treatment efficacy based upon clinical seizure reduction, side effects of quinidine therapy, and variant-specific responsiveness to treatment. Quinidine treatment resulted in a > 50% seizure reduction in 20% of patients, with rare patients achieving transient seizure freedom. Multiple other therapies demonstrated some success in reducing seizure frequency, including the ketogenic diet and vigabatrin, the latter particularly in patients with epileptic spasms. Patients with the best quinidine response had variants that clustered distal to the NADP domain within the RCK2 domain of the protein. Half of patients did not receive a quinidine trial. In those who did, nearly half did not achieve therapeutic blood levels. More favorable response to quinidine in patients with KCNT1 variants distal to the NADP domain within the RCK2 domain may suggest a variant-specific response.